All Days 2014
DOI: 10.2118/171539-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluids Application for Heavy Oil Recovery

Abstract: The application of nanotechnology in the oil industry has become a useful approach in oil production. The main objective of this study is to investigate the effects of nanofluids on the recovery of heavy crude oil compared to water flooding. The nanofluids are prepared by the addition of pure and mixed nanoparticles; Silicon oxide, Aluminum oxide, Nickel oxide, and Titanium oxide at different concentrations to the saline water. The prepared nanofluids were screened to determine the suitable type for the heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…Finally, this review identifies the challenges and opportunities for future study regarding application of nanoparticles in EOR processes. [16].…”
Section: Low Costs and Environmental Friendlinessmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, this review identifies the challenges and opportunities for future study regarding application of nanoparticles in EOR processes. [16].…”
Section: Low Costs and Environmental Friendlinessmentioning
confidence: 99%
“…Therefore, SiO2 nanofluid had the potential to produce more oil from reservoirs. Alomair et al [16] furthered to compare the ability of three NPs (Al2O3, SiO2 and NiO) to reduce IFT between the crude oil and nanofluids. They found that the SiO2 NPs resulted in the lowest IFT value and NiO had the lowest reduction on IFT.…”
Section: Ift Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three extraction phases categorised as primary, secondary and tertiary recovery. Primary and secondary recovery uses conventional methods such as thermal heating, water flooding and carbon dioxide injection [1]. Because of the highly viscous properties of the crude oil flowing after the secondary recovery phase, the mobility of the fluid is greatly reduced and thus requires alternative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluid is a synthesized fluid, which exhibit superiors heat transfer performance and high adaptability in various oil and gas operations [1,2]. Ferrofluid, a type of nanofluids, is made up of non-magnetic bases fluids and dispersed iron nanoparticle of diameter lesser than 100 nm with a surfactant layer coat.…”
Section: Introductionmentioning
confidence: 99%